The potential role of preventive and therapeutic immunonutrition strategies for pediatric food allergy: A mini-review - Coppola, Serena; Carucci, Laura; De Michele, Roberta; Berni Canani, Roberto (Frontiers in Nutrition, 2022)
Food allergy (FA) represents one of the main chronic conditions of the pediatric population. The gut microbiome (GM)-immune system axis is a milestone in affecting FA susceptibility. The dynamic and bidirectional crosstalk between the GM and immune system starts early in life, and it is deeply modulated during the first 1,000 days of life. Nutritional factors during this crucial period mainly influence the proper GM-immune system development and function across the lifespan, with potential beneficial or detrimental effects on health status. Immunonutrition strategies, applied from conception, could represent an innovative target for prevention and treatment of pediatric FA. Here we described the potential role of preventive and therapeutic immunonutrition strategies for pediatric FA, highlighting putative future perspectives in this field.